Effects of amount and frequency of nitrogen supplementation on nutritional performance and metabolism in cattle fed medium-quality tropical forage - Luana Marta de Almeida Rufino; João Paulo Pacheco Rodrigues; Marcia de Oliveira Franco; Nicole Stephane de Abreu Lima; Luiz Carlos de Oliveira Sousa; Claudia Batista Sampaio; Edenio Detmann (Discover Animals)
Abstract We aimed to evaluate how the amount and frequency of nitrogen (N) supplementation impact nutritional performance and metabolism in cattle fed medium-quality tropical forage. Five young Nellore × Holstein bulls (262 ± 20 kg) were used in a 5 × 5 Latin square design. The basal diet consisted of medium-quality signal grass hay, with the following treatments: (1) control, without supplementation; (2) daily supplementation with 30% of rumen degradable protein (RDP) requirements; (3) supplementation every three days with 30% of RDP requirements; (4) daily supplementation with 60% of RDP requirements; and (5) supplementation every three days with 60% of RDP requirements. Overall, there was no effect (p ≥ 0.38) of N supplementation on voluntary intake, though infrequent supplementation reduced (p ≤ 0.04) voluntary intake. N supplementation improved (p ≤ 0.03) crude protein digestibility without affecting fibre digestibility (p ≥ 0.17). Supplementation frequency did not affect (p ≥ 0.08) digestibility characteristics. There were no effects (p ≥ 0.06) of treatments on N retention or utilisation efficiency. However, interactions between treatments and supplementation cycle days were detected (p ≤ 0.01) for both ruminal ammonia N (RAN) and serum urea N (SUN) concentrations, with RAN peaking on the first day for infrequently supplemented animals, while SUN peaked on the second day for cattle receiving 60% RDP infrequently. This decoupling between RAN and SUN concentrations suggests a potential mechanism for conserving dietary N with infrequent supplementation. Reducing N supplementation frequency decreases voluntary intake in cattle fed medium-quality tropical grass, but does not impair digestion, N utilisation, or metabolism.